EFEKTIVITAS PROYEK-PILAH YAYASAN BINTARI DAN USAID DALAM PENANGANAN SAMPAH DI KOTA SEMARANG - Alamsyah "; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The waste problem in Indonesia has increased with a bad record as the second largest waste contributor country after China. The city of Semarang is one of the cities in Indonesia that has the highest landfill of several districts/cities in Central Java Province. The BINTARI Foundation as an NGO concerned with environmental issues in the City of Semarang collaborates with USAID MWRP to improve the performance of the waste bank and increase waste recycling through the PILAH project. This study will analyze the effectiveness of the BINTARI Foundation and USAID's PILAH project in contributing to waste management in Semarang City. This research uses qualitative research methods, with primary data collection techniques sourced from interviews with the BINTARI Foundation and several Waste Bank administrators in Semarang City, then secondary data obtained from document studies by browsing books, journals, research documents, articles, and websites that are considered relevant author. This study also uses the perspective of Green Thought Effectiveness Theory and Foreign Aid Concept. This study shows results based on effectiveness theory using 4 indicators including achievement, timeliness, benefits, and results that the PILAH Project in Semarang City is considered effective and brings changes from the economic, social and environmental side. The first is from an economic perspective, where people such as customers and waste bank activists get incentives for collecting consumable plastics. Second, from the social side, there is a change in people's behavior towards the importance of protecting the environment by sorting garbage from homes so it doesn't leak into the sea. Third, from the environmental side, namely the presence of waste management upstream or households contributing to reducing pollution of downstream ecosystems. Keywords: Semarang City Waste Management,, BINTARI Foundation, USAID, MWRP, PILAH Project.